Sedimentology and composition of the Takrouna Formation, northern Victoria Land, Antarctic: provenance and depositional evolution of a Permian Gondwana basin - John, Nadine (2014)
During the late Paleozoic a series of sedimentary basins occupied the eastern margin of Gondwana that is considered as long-lasting subduction-related plate boundary. Nature, evolution and provenance of some of these basins, for example of the Permian Victoria Basin in the Ross Sea sector of East Antarctica, are still poorly understood. The up to 300 m thick succession of siliciclastic sedimentary rocks of the Permian Takrouna Formation in northern Victoria Land represents the fossil record of the northern part of this basin system, exposed within an outcrop belt with an extension of 125 × 160 km. This study presents a detailed description of the spatial and temporal evolution of the Permian Takrouna Formation. The reconstruction of the source areas and the depositional evolution of the continental Victoria Basin contribute to a broader understanding of the tectonic regime at the eastern margin of Gondwana during the Permian. Based on the investigations of vertical and lateral sections in six mountain ranges the development of sedimentary architecture and facies was reconstructed. The combination of sedimentological, petrographic and geochemical methods has been used to determine the controls on deposition and provenance. Petrographic and geochemical tools include the study of heavy and light mineral assemblages, the cathodoluminescence of detrital quartz, the whole-rock geochemical composition of sandstones and mudstones, the composition of selected minerals, as well as U-Pb age dating of detrital zircons. Further a petrographic and geochemical characterization of the abundant organic material has also been used to investigate the depositional environment and also the thermal history of the succession. The integration of this data set and comparison to the data gained from selected samples of the Permian Weller Coal Measures in southern Victoria Land enable a paleogeographic reconstruction of the Victoria Basin and the drainage system that occupied the study area